POLA HIDUP KOMUNITAS GUA HUNIAN PRASEJARAH KAWASAN KARST BLORA - Nurani, Indah Asikin (BRIN, 2010)
Blora limestone region is an important area where several prehistoric sites, occupied continuously during the Late Pleistocene to Early Holocene, are discovered. The Pleistocene sites are found in the southeast part of the Blora regency and the ear1y Holocene sites are located in the District of Todanan, in the western part of the regency. One of the most interesting sites situated in this area is the Kidang cave. It is the only limestone cave which shows traces of human occupation in this area. This paper will discuss about the possible adaptation as well as occupation patterns in Kidang Cave.